1944
DOI: 10.1111/j.1365-2621.1944.tb16686.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF TEMPERATURES APPROXIMATING 0°C. UPON GROWTH AND BIOCHEMICAL ACTIVITIES OF BACTERIA ISOLATED FROM MACKEREL1

Abstract: The work herein described was undertaken in connection with a study of the effect of fast-freezing upon the bacterial flora of mackerel. The purpose of the experiments was to ascertain the effects of the low temperatures used in the process upon-the characteristics of growth of these bacteria which represent a major portion of the bacterial flora of the fish. RELATIONSHIP BETWEEN GROWTH OF BACTERIAL FLORA OF MACKEXEL AND A RANGE OF TEMPERATURE' This work was aided by an Ellen Browning Scripps Fellowship. a Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1949
1949
1968
1968

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Using stationary-phase cells as an example, it may be seen that at 0 C Lockhart's lag ranged between 72 and 80 hr, at 2.5 C from 40 to 48 hr, at 5 C from 30 to 38 hr, at 7.5 C from 22 to 26 hr, and at 10 C the lag decreased to 14 to 17 hr, depending on the growth temperature of the inoculum. This effect agrees with the reports of Hess (1934), Kiser (1944), and Lawton and Nelson (1955) working with other organisms and under different conditions. This result is also in agreement with the work of Martin (1932) and Walker et al (1934), who have shown that the rate of metabolic activity increases as the temperature of growth increases.…”
supporting
confidence: 93%
“…Using stationary-phase cells as an example, it may be seen that at 0 C Lockhart's lag ranged between 72 and 80 hr, at 2.5 C from 40 to 48 hr, at 5 C from 30 to 38 hr, at 7.5 C from 22 to 26 hr, and at 10 C the lag decreased to 14 to 17 hr, depending on the growth temperature of the inoculum. This effect agrees with the reports of Hess (1934), Kiser (1944), and Lawton and Nelson (1955) working with other organisms and under different conditions. This result is also in agreement with the work of Martin (1932) and Walker et al (1934), who have shown that the rate of metabolic activity increases as the temperature of growth increases.…”
supporting
confidence: 93%
“…Secondly, above or below the range of optimal activity, there in turn may be variation in Q10 values-as with chemical reactions-according to the particular temperature range involved (Ingraham and Bailey, 1959 ;Jezeski and Olsen, 1961;Kiser, 1944 ;Sizer and Josephson, 1942). Even for chemical reactions, Qlo values sometimes hold true only for relatively narrow temperature ranges, and generally only for the same substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial count increases steadily throughout iced storage and bacterial decomposition of fish flesh does occur a t 0°C.(32"F. ), Griffiths and Stansby (1934), Kiser (1944), Reay (1935), and Shewan (1944).…”
Section: Bacteriology O F S H R I M P 373mentioning
confidence: 99%